Sand Mining Impact On Revenues Fishermen In The District Tambang Kampar District Province Riau - Melda Yanti; Hamdi Hamid; Lamun Bathara (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted in March 2014, which took place in the District Mine Kampar district in Riau Province. This study aims to: Knowing the characteristics of fishing communities, Knowing the impact caused by sand mining on the existence of fishing effort, Knowing the impact caused by sand mining on the income of fishermen, Knowing what strategies do people in mehadapi this problem.This study uses survey data collection techniques using questionnaires to selected respondents where respondents of 16 people, 13 fishermen and three sand miners. Sand miners affect the number of fishermen, fishing gear and fish catches are steadily decreasing. Economic impact: reduced revenue in the field of fisheries, namely: the average income of the fisheries sector before the sand mining operation is Rp 1.73 million and after the sand Mining decrease the average income in the fisheries sector to Rp 1,100,000.Keywords: Sand Mining, Revenue Fishermen, District Tambang